2017
DOI: 10.1093/nutrit/nuw047
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to promote physical activity in Mexican elementary school students: building public policy to prevent noncommunicable diseases

Abstract: Physical activity is an important component of strategies for health promotion and prevention of noncommunicable diseases. It is also associated with decreased risk for cardiovascular disease in overweight and obese adults and children. This article addresses the initial description of a physical activity intervention for children attending public elementary schools in Mexico. The objective was to develop a replicable model based on a strategic public, private, academic, and social partnership that would have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Their results showed significant improvements (p < 0.05) in triglycerides, glycemia, and oxygen saturation; higher prevalence of normal cholesterol levels, blood pressure, and body mass; better habits and better quality of diet (20). Their findings match those presented by Polo-Ateiza et al, who conducted an intervention for over 20,000 Mexican children in five schools consisting in children participation in supervised medium-effort physical activity for 30 minutes daily, five days a week for a year and achieved a 31.9 % reduction in overweight and obesity indexes, better levels of glycemia and lipidic profile (21). These two studies show a positive effect that agree with our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Their results showed significant improvements (p < 0.05) in triglycerides, glycemia, and oxygen saturation; higher prevalence of normal cholesterol levels, blood pressure, and body mass; better habits and better quality of diet (20). Their findings match those presented by Polo-Ateiza et al, who conducted an intervention for over 20,000 Mexican children in five schools consisting in children participation in supervised medium-effort physical activity for 30 minutes daily, five days a week for a year and achieved a 31.9 % reduction in overweight and obesity indexes, better levels of glycemia and lipidic profile (21). These two studies show a positive effect that agree with our findings.…”
Section: Discussionsupporting
confidence: 81%
“…A review study showed that long-term interventions in Mexican children based in Mexico or the United States changed adiposity markers when nutrition and physical activity were modified 37 . A 12-week physical activity intervention in Mexican children did not modify BMI but decreased biochemical parameters such as blood glucose and cholesterol concentrations 38 . Therefore, a long-term multidimensional intervention that includes a more significant number of children could better impact the Mexican population in the future.…”
Section: Discussionmentioning
confidence: 88%
“…No statistically significant BMI or obesity prevalence changes were reported in 6/13 of the studies (Arroyo & Fig. 2 Map from the origin of the included interventions Carrete, 2018;Cruz-Bello et al, 2019;Elizondo-Montemayor et al, 2014;Perichart-Perera et al, 2008;Polo-Oteyza et al, 2017;Vazquez et al, 2017). But some studies (5/13) reported significant reductions in BMI (Rodriguez-Ventura et al, 2018;Saucedo-Molina et al, 2018;Zacarias et al, 2019) or obesity prevalence (Balas-Nakash et al, 2010;Rios-Cortazar et al, 2013).…”
Section: Changes In Anthropometric Outcomesmentioning
confidence: 98%
“…Concerning the studies' funding, nine (31.0%) did not report any funding, and only one (Arroyo et al, 2018) reported not receiving any funding for the study. Three studies (10.3%, Gatica-Dominguez et al, 2019;Perichart-Perera et al, 2008;Polo-Oteyza et al, 2017) reported receiving funding from the food industry, three more (10.3%; Costa-Urrutia et al, 2019;Ramirez-Lopez et al, 2005;Levy et al, 2012a, b) reported using funds from local authorities. Five studies (17.2%; Mejia et al, 2016;Padilla-Raygoza et al, 2013;Rodriguez-Ventura et al, 2018;Salazar-Vazquez et al, 2016;Zacarias et al, 2019) reported using public national funding, and five more (Alvirde-Garcia et al, 2013;Bacardi-Gascon & Jiménez-Cruz 2012;Benitez-Guerrero et al, 2016;Martinez-Andrade et al, 2014;Vilchis-Gil et al, 2016) received funding from public institutions (e.g., public hospitals or public universities).…”
Section: Quality and Risk Of Bias Appraisalmentioning
confidence: 99%